Platelets promote human macrophages-mediated macropinocytosis of Clostridioides difficile - Barbero, Angela María; Hernández Del Pino, Rodrigo Emanuel; Fuentes, Federico; Barrionuevo, Paula; Pasquinelli, Virginia (Frontiers in Cellular and Infection Microbiology, 2024)
Clostridioides difficile is the main causative agent of hospital-acquired diarrhea and the potentially lethal disease, C. difficile infection. The cornerstone of the current therapy is the use of antibiotics, which is not fully effective. The molecular mechanisms, inflammatory conditions and host-immune responses that could benefit the persistence or elimination of C. difficile remain unclear. Macrophages perform different ways of endocytosis as part of their immune surveillance functions and platelets, classically known for their coagulatory role, are also important modulators of the immune system. The aim of this study was to evaluate the endocytosis of vegetative C. difficile by human macrophages and the involvement of platelets in this process. Our results showed that both macrophages and platelets interact with live and heat-killed C. difficile. Furthermore, platelets form complexes with human monocytes in healthy donor's fresh blood and the presence of C. difficile increased these cell-cell interactions. Using flow cytometry and confocal microscopy, we show that macrophages can internalize C. difficile and that platelets improve this uptake. By using inhibitors of different endocytic pathways, we demonstrate that macropinocytosis is the route of entry of C. difficile into the cell. Taken together, our findings are the first evidence for the internalization of vegetative non-toxigenic and hypervirulent C. difficile by human macrophages and highlight the role of platelets in innate immunity during C. difficile infection. Deciphering the crosstalk of C. difficile with immune cells could provide new tools for understanding the pathogenesis of C. difficile infection and for the development of hostdirected therapies.